Differential susceptibility of Conyza bonariensis biotypes to glyphosate and ALS-Inhibiting herbicides in Argentina - Puricelli, Eduardo Carlos Jose Maria; Faccini, Delma Edith; Metzler, Marcelo; Torres, Patricia Susana (Scientific Research Publishing, 2018)
The aim of this study was to compare control of three stages biotypes (rosette, bolting, and repro- ductive stage) of Conyza bonariensis glyphosate susceptible biotype (S) and tolerant biotype (T) to glyphosate with glyphosate and mixtures of acetolactate synthase (ALS)-inhibiting. For glyphosate, the dose-response curves confirmed that injury of the biotype T relative to biotype S was signifi- cantly lower for both rosette and bolting stages. Resistance index (RI) for this herbicide was approximately 4 for both weed stages. At bolting, for both biotypes doses much higher than the recommended dose were required. For acetolactate synthase (ALS)-inhibiting herbicides, at the rosette stage, control of both biotypes was excellent with doses significantly lower than the recommended rate. All herbicides within this group showed a very low I50 relative to the recommended rate. These results indicate that biotypes difficult to control with glyphosate at the rosette and bolting stage may be controlled using acetolacte synthase (ALS)-inhibiting herbicides. Control for the reproductive stage was poor. A management program based on the combination of glyphosate with pre- and post-emergence acetolactate synthase (ALS) herbicides may be effective to control the weed.